Increased glial-derived neurotrophic factor in the small intestine of rats infected with the tapeworm, Hymenolepis diminuta - Starke-Buzetti, Wilma Aparecida [UNESP]; Oaks, John A. (Wiley-Blackwell, 2008)
The neurotrophin, glial-derived neurotrophic factor (GDNF), is essential for the development of the enteric nervous system (ENS) in both the embryo and neonate and may be important for maintenance and plasticity of ENS. The tapeworm, Hymenolepis diminuta, altered the number of cells containing GNDF in the host's jejunum and ileum. Numbers and locations of GDNF-containing cells were determined by applying monoclonal anti-GDNF antibody to intestinal segments collected from infected and uninfected age-matched rats during the initial 34 days post-infection (dpi). Most cells staining positive for GDNF were present in the lamina propria of the jejunum and ileum from both infected and uninfected rats. The co-localization of staining by the antibodies, anti-GDNF and anti-ED2 (a nuclear specific antibody for resident macrophages) indicated that at least 74% of the cells staining for GDNF were macrophages. Mast cells did not stain with the anti-GDNF antibody. The increased number of GDNF+ cells in the infected rat intestine suggests that this neurotrophin may play a role in the neural and mucosal responses to lumenal tapeworm infection.
Keywords: ED2; GDNF; macrophages; mast cells; tapeworm